If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = x(95 + -4x) 0 = (95 * x + -4x * x) 0 = (95x + -4x2) Solving 0 = 95x + -4x2 Solving for variable 'x'. Remove the zero: -95x + 4x2 = 95x + -4x2 + -95x + 4x2 Reorder the terms: -95x + 4x2 = 95x + -95x + -4x2 + 4x2 Combine like terms: 95x + -95x = 0 -95x + 4x2 = 0 + -4x2 + 4x2 -95x + 4x2 = -4x2 + 4x2 Combine like terms: -4x2 + 4x2 = 0 -95x + 4x2 = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-95 + 4x) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-95 + 4x)' equal to zero and attempt to solve: Simplifying -95 + 4x = 0 Solving -95 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '95' to each side of the equation. -95 + 95 + 4x = 0 + 95 Combine like terms: -95 + 95 = 0 0 + 4x = 0 + 95 4x = 0 + 95 Combine like terms: 0 + 95 = 95 4x = 95 Divide each side by '4'. x = 23.75 Simplifying x = 23.75Solution
x = {0, 23.75}
| 5-m=-11-5m | | 4z^-1/8(3z^7-z^-1/8) | | 2x^2+8x+3x+12=0 | | 4n+8-4n=14+6n | | (5a^6b^2-15a^3b^5)/(5a^5b^3) | | 56+x+6=180 | | 144=x+2+x+3 | | 3x+5y=65 | | 6-6n=-6-2n | | 7t-3=2(t+1)+2 | | 3x+4x-5=37 | | -5k+3k=-4k+2 | | 15x+20y=875 | | x+-3-3=-6 | | R(x)=x(95-4x) | | x^2+3x-127=0 | | 4+a-8a=-17 | | 80+95+x+38=180 | | n*6=24+n | | 13x-5x+6-2x= | | 7(-5x+5)=0 | | 90+90+128+x=180 | | 1-5x-2x=15 | | x^2+y^2+8x+4y= | | 15(3x+1)+20(3(3x+1))-5=875 | | 6x-(5x+9)=5x-29 | | 7m-20=2m | | 110+35+x+12=180 | | 8-7r+7=1 | | -6(6x-8)+5=-36x+53 | | 3k+8-k=0 | | -3y+15=2y-10 |